ACO1 and IREB2 downregulation confer poor prognosis and correlate with autophagy-related ferroptosis and immune infiltration in KIRC - Zhu, Ting; Xiao, Zhuoyu; Yuan, Haoyu; Tian, Hu; Chen, Taoyi; Chen, Qi; Chen, Mingkun; Yang, Jiankun; Zhou, Qizhao; Guo, Wenbin; Xue, Kangyi; Xia, Ming; et al. (Frontiers in Oncology, 2022)
Background: ACO1 and IREB2 are two homologous cytosolic regulatory proteins, which sense iron levels and change iron metabolism-linked molecules. These two genes were noticeable decreased in Kidney Renal Clear Cell Carcinoma (KIRC), which confer poor survival. Meanwhile, there is a paucity of information about the mechanisms and clinical significance of ACO1 and IREB2 downregulation in renal cancers. Methods: The expression profiles of ACO1 and IREB2 were assessed using multiple public datasets via several bioinformatics platforms. Clinical and pathological information was utilized to stratify cohorts for comparison. Patient survival outcomes were evaluated using the Kaplan-Meier plotter, a meta-analysis tool. The correlations of ACO1 and IREB2 with ferroptosis were further evaluated in TCGA-KIRC database. Tumor immune infiltration was analyzed using the CIBERSORT, TIMER and GEPIA data resource. ACO1 antagonist sodium oxalomalate (OMA) and IREB2 inhibitor sodium nitroprusside (SNP) was used to treat renal cancer ACHN cells together with Sorafenib. Results: Kidney Renal Clear Cell Carcinoma (KIRC) patients with low ACO1 or IREB2 contents exhibited a remarkably worse survival rate in contrast with those with high expression in Kaplan-Meier survival analyses. Meanwhlie, ACO1 and IREB2 regulate autophagy-linked ferroptosis along with immune cell invasion in tumor microenvironment in KIRC patients. Blocking activation of these two genes by its inhibitors OMA or SNP ameliorated Sorafenib-triggered cell death, supporting that ACO1 and IREB2 could be participated in its cytotoxic influence on renal cancer cells. Conclusion: ACO1 and IREB2 downregulation in renal cancers correlated with cancer aggressiveness, cellular iron homeostasis, cytotoxic immune cell infiltration, and patient survival outcomes. Our research is integral to verify the possible significance of ACO1 and IREB2 contents as a powerful signature for targeted treatment or novel immunotherapy in clinical settings.